Functionalization of Carbon Electrodes with Nanotitania by Atomic Layer Deposition - Graciano B. De Souza; Dachamir Hotza; Rolf Janßen; Kaline P. Furlan; Carlos R. Rambo (Advances in Materials Science and Engineering)
Carbon fibers are materials with a very high surface area and are interesting for applications such as filters, fire-resistant heat insulation, photocatalysis, and capacitor electrodes. Moreover, thermal burnout can easily remove these fibers, making them ideal templates for high-precision coatings or keeping them within the coated structure, generating nanostructured composites. In this work, two different substrates, carbon felt and bacterial nanocellulose were coated by TiO2 with atomic layer deposition (ALD). After deposition, the templates were pyrolyzed or further removed by burnout in the air. The microstructure evolution of the 3D interlocked-fibers structures was characterized by scanning electron microscopy and nitrogen adsorption surface area after each step. Stable anatase was present as a single TiO2 phase even after heat treatment at 800°C. Moreover, electrochemical impedance spectroscopy and constant current charge-discharge were employed to investigate the electrochemical properties of the samples. Our results show that all samples display a uniform layer after ALD and that the surface area decreases with an increasing number of ALD cycles. After burnout, the 3D structures presented a straw-like appearance to the shells. Nonetheless, both samples presented a power density comparable to a porous NiO/C, with the pyrolyzed bacterial nanocellulose sample displaying a higher pseudocapacitance performance than the carbon-felt samples.